Disentangling the intragroup HI in Compact Groups of galaxies by means of X3D visualization. Issue Volume 11:Issue S321(2015) (21st March 2017) - Verdes-Montenegro, Lourdes; Vogt, Frederic; Aubery, Claire; Duret, Laetitie; Garrido, Julián; Sánchez, Susana; Yun, Min S.; Borthakur, Sanchayeeta; Hess, Kelley; Cluver, Michelle; del Olmo, Ascensión; Perea, Jaime
Abstract: As an extreme kind of environment, Hickson Compact groups (HCGs) have shown to be very complex systems. HI-VLA observations revealed an intrincated network of HI tails and bridges, tracing pre-processing through extreme tidal interactions. We found HCGs to show a large HI deficiency supporting an evolutionary sequence where gas-rich groups transform via tidal interactions and ISM (interstellar medium) stripping into gas-poor systems. We detected as well a diffuse HI component in the groups, increasing with evolutionary phase, although with uncertain distribution. The complex net of detected HI as observed with the VLA seems hence so puzzling as the missing one. In this talk we revisit the existing VLA information on the HI distribution and kinematics of HCGs by means of X3D visualization. X3D constitutes a powerful tool to extract the most from HI data cubes and a mean of simplifying and easing the access to data visualization and publication via three-dimensional (3-D) diagrams.